2017
DOI: 10.1111/aec.12489
|View full text |Cite
|
Sign up to set email alerts
|

Ecological consequences of an unusual simultaneous masting of Araucaria araucana and Chusquea culeou in North‐West Patagonia, Argentina

Abstract: A simultaneous masting of two abundant species in the temperate forests of North-West Argentinean Patagonia occurred in 2013 for the first time ever recorded: the semelparous bamboo grass Chusquea culeou (colihue), dominating the understory, flowered and set seed across 1100 km 2 while pehu en (Araucaria araucana), an endemic conifer co-dominating the tree layer had the highest regionally synchronized mast event in the last 30 years. Strong trophic effects were expected as a consequence of this extraordinary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
0
0
3
Order By: Relevance
“…This is in contrast to lowland irrigated rice cropping, which is usually conducted over much larger land areas (>5 ha) and where rodent pest numbers can be facilitated by growing 2-3 crops per annum. Rodent trap success in our study is similar to that observed in upland areas of Laos (Brown and Khamphoukeo, 2010;Jäkel et al, 2017Jäkel et al, , 2016 and other forest habitats in Uganda, Argentina and Madagascar (Kasangaki et al, 2003;Milesi et al, 2017;Stephenson, 1994). compared to 2010, resulting in slightly later harvests during 2010 (Holland et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…This is in contrast to lowland irrigated rice cropping, which is usually conducted over much larger land areas (>5 ha) and where rodent pest numbers can be facilitated by growing 2-3 crops per annum. Rodent trap success in our study is similar to that observed in upland areas of Laos (Brown and Khamphoukeo, 2010;Jäkel et al, 2017Jäkel et al, , 2016 and other forest habitats in Uganda, Argentina and Madagascar (Kasangaki et al, 2003;Milesi et al, 2017;Stephenson, 1994). compared to 2010, resulting in slightly later harvests during 2010 (Holland et al, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Entre 2020 y 2030, frente a la próxima floración de los bambúes, esta especie podría experimentar un riesgo elevado de escasez de alimento en su hábitat fragmentado, sin posibilidad de traslado a zonas circundantes. En América del Sur, varias especies de aves especialistas en bambúes sufren una fluctuación marcada en sus fuentes de hábitat y de alimento (Areta et al 2009(Areta et al , 2013(Areta et al , 2016Areta and Cockle 2012;Cockle and Areta 2013;Milesi et al 2017).…”
Section: C������������ �� ��� ����������� �� ��� �������unclassified
“…La floración y la fructificación masiva de una especie de bambú produce grandes cantidades de semillas que quedan disponibles en el ambiente para la fauna granívora nativa, en su mayoría roedores (González and Donoso 1999). Estos disfrutan de este extraordinario suministro de alimento, lo cual provoca que aumente aceleradamente su densidad poblacional; ello desencadena un fenómeno conocido en todo el planeta, y que en América del Sur recibe el nombre de 'ratadas' (Gallardo and Mercado 1999;Jaksic and Lima 2003;Milesi et al 2017;Murúa et al 1996;Piudo et al 2005;Piudo and Monteverde 2016). Las ratadas y su relación con las floraciones masivas de bambúes se documentaron en la literatura desde el 1800 (Jaksic and Lima 2003).…”
Section: ₂₆₇unclassified
“…LOS IMPACTOS DE LA FLORA Y FAUNA EXÓTICA INVASORA EN EL ECOSISTEMA DEL PEWÉN La invasión de fauna y flora exóticas ha captado la preocupación de científicos y pobladores más recientemente. Entre la fauna, se han estudiado principalmente las interacciones entre el pewén y la granivoría por el jabalí (Sus scrofa, Linneaus, 1758) y por la rata noruega (Rattus norvegicus, Berkenhout, 1769) (Skewes et al 2007, Sanguinetti y Kitzberger 2010, Tella et al 2016, Milesi et al 2017. Estas especies se distribuyen sobre gran parte del ecosistema, incluso en bosques sin actividades humanas, y consumen una gran proporción de semillas (e.g.…”
Section: Efectos De La Herbivoría Y Granivoría Del Ganado Y Del Human...unclassified